Research–Practice Partnerships in Education in Sudan: Educators’ Perspectives on Opportunities and Challenges - Ahmed Mansour Mohammad Gasmelseed (Journal of Pedagogy and Education Science, 2026)
The purpose of this study was to examine Sudanese educators' perceptions of the RPPs in education, including the difficulties and possibilities they present. The study used a qualitative approach, using interviews as the data collection method, with five educators who have research experience. The participants' responses show that building trust in RPPs relies on shared research priorities, transparent research processes, mutual respect, and active teacher involvement at every stage of the research process. The findings also suggest that effective partnerships require strong communication skills, the ability to connect theory with practice, and clearly defined roles and responsibilities for both researchers and practitioners. However, obstacles such as contrasting priorities, limited time and incentives for teachers, a weak culture of applied research, and insufficient funding may impede the implementation of these joint efforts. It is recommended that policymakers develop explicit policies to promote research collaborations between university researchers and school teachers, and provide the necessary training and assistance to ensure their success.